Biocompatible caramelized carbonaceous nanospheres supported paramagnetic ultrathin manganese oxide nanosheets via self-sacrificing reduction as a MRI contrast agent for liver imaging. (December 2016) - Guo, Weihua; Qi, Yafei; Zhang, Yuqiang; Ma, Long; Yu, Dexin; Zhan, Jinhua
Abstract: The elimination of nanoparticles remains the major roadblock to clinical translation. Caramelization reaction is a general type of non-enzymatic browning reactions to food caramels, the products of carbonaceous nanospheres can be considered safe for biological applications. Here, we report a biocompatible caramelized carbonaceous nanospheres supported paramagnetic ultrathin manganese oxide nanosheets via self-sacrificing reduction as a liver MRI contrast agent and for T1 -weighted MR imaging, which are taken up by Kupffer cells resulting in a high relaxivity rate. Mn3 O4 -caramelized nanoparticles (Mn3 O4 -CNPs) were synthesized and their characteristics as MR contrast agents were investigated. The relaxation rate (r1 ) of Mn3 O4 -CNPs is calculated to 11.6 mM −1 s −1 by Mn concentrations and is nearly three times commercial Gd III -based complex agents at a 3.0 T clinical MR scanner, and the in vivo experiment shows that the signals of mouse liver increase by 50.1% under T1 -weighted imaging in 4 h post-injection of Mn3 O4 -CNPs. The in vivo bio-distribution reveals that the concentrations of Mn are equal to the pre-injection after post-injection of Mn3 O4 -CNPs 48 h. Therefore, the Mn3 O4 -CNPs can be used as biocompatible liver MR contrast agents. Graphical abstract: